Assessing the circularity of transportation fuel production systems - Axel Lindfors; Roozbeh Feiz; Sofia Poulikidou; Tomas Lönnqvist; Anton Fagerström; Mark Sanctuary (Energy, Sustainability and Society)
Abstract Background The circular economy represents a vision of ever-increasing importance for policy making. In this paper, the circularity of transportation fuel production systems is explored, as energy carriers are seldom the focus of existing methods. A theoretical framework for understanding the circularity of energy carriers was devised based on the renewability and secondary fractions of inputs and the recycling of outputs, which cover both biological and technical cycles. Based on this framework, and with input from actors working in the field of transport fuels, a six-step method was developed to assess the circularity of energy carriers. The method uses a life cycle perspective for assessing energy carriers across their life cycle. Results This method was applied to four production systems in the Swedish context: hydrogenated vegetable oil (HVO) from tall oil, ethanol from forest residues, biomethane from household food waste, and battery–electric mobility. The results showed that all studied biofuels have a high degree of circularity due to the use of secondary materials as a feedstock. The biomethane system scored the highest percentage, with a circularity score of 81%, while the HVO and ethanol systems only reached a score of 75% and 45%, respectively. The battery–electric system, on the other hand, performed worse at only 17% circularity due to the low degree of circularity in the battery production. One “greening” scenario was tested for each production system to explore the impact of possible future improvements. Conclusions The results showed that second-generation biofuels align well with the circular economy concept as they upcycle low-value resources into high-value products. At the same time, electric mobility requires a higher degree of material recirculation to further align it with the circular economy. Furthermore, all production systems indicated improvement potentials and should, therefore, be aimed at increasing their recirculation rates and use of renewable resources. In conclusion, this article gives valuable input into the broader decision process to determine which fuels should be promoted during the transition away from fossil fuels, as circularity is one aspect to be considered.